Pengetahuan Siswi terhadap Kejadian Anemia dengan Asupan Zat Besi (Fe), Vitamin C di SMP Negeri 5 Makassar Tahun 2024 - Tenriawi, Westy; Kurniati HM, Ary Herlina (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Anemia is a health problem that often occurs in adolescent girls, including at SMP Negeri 5 Makassar. This study aims to determine the relationship between iron intake, vitamin C, and knowledge of female students with the incidence of anemia in adolescent girls at SMP Negeri 5 Makassar. The research method used was an analytical study with a cross-sectional design. The research sample was taken using proportional random sampling with a total of 65 female students. Data were collected through measurement of iron and vitamin C intake using Semi Quantitative Food Frequency Questionnaires (SQFFQ) interview form, and knowledge of schoolgirls using questionnaires. The results showed no relationship between iron intake (p=1.000), vitamin C (p=0.333) and knowledge of schoolgirls (p=1.000 with the incidence of anemia in adolescent girls. Recommendations from this study are the need to increase understanding of the importance of iron and vitamin C intake and knowledge about anemia in adolescent girls through more intensive counseling and education in the school environment. It is hoped that the results of this study can be the basis for the development of more effective intervention programs in overcoming the problem of anemia in adolescent girls as well as identifying other factors that may contribute to the incidence of anemia in adolescent girls, such as diet, physical activity, genetic factors and iron inhibitor factors.Limitations of the study included difficulties in drawing blood from overweight girls or those who could not find veins in their hands, girls who fainted before the blood drawing process and girls who chose to withdraw from the study.